The Relationship between Spirituality and Duration of Infection with the Quality of Life in People with HIV/AIDS - Sukma, Komang Ayi; Sunarsih, Sunarsih; Rahmawati, Rahmawati (Magister Kesehatan Universitas Mandala Waluya, 2023)
Backgrounds: HIV/AIDS has become an emergency problem throughout the world, where there is still high transmission of infection, morbidity, and mortality. Based on data obtained at the VCT Clinic at the Kendari City Hospital, over the past 5 years, there has been an increase in new cases, where at the end of 2022 it is known that the HIV/AIDS Incidence Rate is 183/100,000. This study aims to analyze the determinants of quality of life in people with HIV/AIDS at the VCT Clinic at Kendari City Hospital. Methods: The type of research used in this research is quantitative research, using a cross-sectional study design. The population in this study was 247 people. The number of research samples is 151 people, with sampling using Simple Random Sampling. Data analysis was carried out descriptively and inferentially using the Chi-Square test. Results: The results showed that there was a relationship between spirituality (X2count = 6.071 > X2table = 3.841), duration of infection (X2count = 6.334 > X2table = 3.841), and the quality of life of PLHIV. Conclusion: There is a relationship between spirituality and duration of infection with the quality of life of PLWHA at the VCT Clinic at Kendari City Hospital.